Alkaline- Anthraquinone Pulpling of Wheat Straw - Bhandari, K. S.; Srivastava, Anita; Sharma, Y. K. (Indian Forester, 1983)
Soda and Soda-Anthrequinone (AQ) pulping of wheat straw were carried out with an aim ie produce pulps for writing and printing papers with fairly good brightness. 11.75,%. active alkali (without AQ) and 10% active alkali (with AQ) produced a pulp of Kappa number 25 Â± 1 at 1665 ’H’ factor with almost identical physico-chemical properties. A gain of 1.8% pulp yield was also observed in latter case. Pulps thus obtained (with and without AQ) have shown almost similar bleaching response. When bleached by C/E/H (5% available chlorine, 2% NaOH extraction/2.5% available chlorine) upto brightness of elrepho 72.9% Â± 0.5. Kraft-AQ pulping (8% active alkali, 8.5% sulphidity) has also been carried out. Under the experimental conditions it was obseryed that the presence of hydrosulphide ion (sulphidity 8.5%) in cooking liquor have shown only slight advantage over soda pulps at same level of active alkali.